Analysis of Teacher Commitment: The Perspective of Altruism and Self-Efficacy in Private Vocational High School - Romaningsih; Azhar; Yuanita, Putri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study examines how altruism and teacher self-efficacy influence teacher commitment in private vocational high schools (SMKS) in Bina Widya District, Pekanbaru. Altruism and self-efficacy are critical because they respectively reflect teachers’ prosocial orientation and confidence to perform instructional tasks—both are expected to support sustained professional commitment. Using an ex-post facto quantitative design, data were collected by questionnaire from a cluster sample of 121 teachers drawn from four SMKS (population = 174). Instruments were pretested (N = 30) and analyzed with SPSS 25 using descriptive statistics and multiple regression (F, t, R²). Results show that altruism and self-efficacy jointly have a positive and significant effect on teacher commitment (F = 53.560, p < .001), explaining 47.6% of variance (R² = .476). Individually, altruism (β = .433, p < .001) and self-efficacy (β = .263, p = .004) also significantly predict commitment. The findings suggest that promoting prosocial values and strengthening teachers’ efficacy beliefs can enhance their professional commitment. Implications for school leaders and policymakers are discussed.